Leveraging Digital Technologies for Strategic Business Development by Millennial Entrepreneurs in Sidenreng Rappang - Putri P, Andi Sri Kumala; Basri, Jumriah; Wirdana, Sri; Putri D, A. Kartini Sari (Newinera Publisher, 2024)
This study examines the business strategies applied by millennial entrepreneurial students in Sidenreng Rappang Regency, South Sulawesi. These students are engaged in various business sectors such as food and beverages, fashion, cosmetics, services, art and design, and digital business. The primary purpose of the study is to analyze the strategies used in responding to business opportunities, competitive advantages, contributions to entrepreneurship learning in higher education, and obstacles and solutions faced by students. With a qualitative phenomenological approach, this study explores the experiences of young entrepreneurs in taking advantage of market opportunities that other entrepreneurs often ignore. Students utilize business model innovation theory by considering factors such as understanding consumer behavior, product differentiation, service quality, and location and network. Entrepreneurship learning in higher education makes an essential contribution to equipping students with an understanding of business strategies and their application in actual practice. Of the ten respondents, five have participated in entrepreneurship seminars and training, while the other five are self-taught and through campus activities. These two methods are considered influential in shaping entrepreneurial skills and mindsets. The challenges faced by millennial entrepreneurs, as well as the solutions they implement, show relevance to modern management theory. This research provides insight into how entrepreneurship education and training can support student business development.